2016
DOI: 10.1016/j.celrep.2016.07.074
|View full text |Cite
|
Sign up to set email alerts
|

Holes in the Glycan Shield of the Native HIV Envelope Are a Target of Trimer-Elicited Neutralizing Antibodies

Abstract: SUMMARY A major advance in the search for an HIV vaccine has been the development of a near-native Envelope trimer (BG505 SOSIP.664) that can induce robust autologous Tier 2 neutralization. Here, potently neutralizing monoclonal antibodies (nAbs) from rabbits immunized with BG505 SOSIP.664 are shown to recognize an immunodominant region of gp120 centered on residue 241. Residue 241 occupies a hole in the glycan defenses of the BG505 isolate with fewer than 3% of global isolates lacking a glycan site at this po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
375
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 224 publications
(408 citation statements)
references
References 55 publications
(90 reference statements)
24
375
3
Order By: Relevance
“…The development of native‐like stabilized trimers has greatly improved our ability to use this method to select for B cells that bind the functional Env trimers as compared with non‐functional forms of Env. However, even with stabilized near‐native trimers as FACS baits, non‐neutralizing binders and strain‐specific nAbs are captured 88, 89. Also, it is important to note that inherently a binding screen will select the best binders for the particular assay used.…”
Section: Discussionmentioning
confidence: 99%
“…The development of native‐like stabilized trimers has greatly improved our ability to use this method to select for B cells that bind the functional Env trimers as compared with non‐functional forms of Env. However, even with stabilized near‐native trimers as FACS baits, non‐neutralizing binders and strain‐specific nAbs are captured 88, 89. Also, it is important to note that inherently a binding screen will select the best binders for the particular assay used.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in the design of immunogens (BG505 SOSIP) that antigenically mimic the HIV envelope glycoprotein (Env) 1 have improved the elicitation of potent isolate-specific Ab responses in rabbits 2 and macaques 3 , but so far failed to induce bnAbs. One possible contributor to this failure is that the relevant antibody repertoires are poorly suited to target somewhat occluded conserved epitope regions on Env relative to exposed variable epitopes.…”
mentioning
confidence: 99%
“…The intentional minimization of such rare amino acids in Mosaic vaccines may help elicit greater breadth of not only T‐cell but also B‐cell responses. Indeed, a recent study showed that Env mosaic vaccines elicited both cellular and humoral responses, and that vaccine‐induced antibodies correlated with protection from acquisition in a SHIV challenge model 28. A second approach to improve induction of cross‐reactive antibodies is based on the idea of tracking B‐cell lineage development in chronically infected subjects who have generated potent and broad neutralizing antibody (bNAb) responses.…”
Section: Vaccine Approaches To Contend With Hiv‐1 Diversitymentioning
confidence: 99%
“…A bivalent mosaic vaccine including pairs of HIV‐1 Gag, Pol, and Env mosaics delivered in adenovirus and poxvirus vectors conferred significant protection against serial, low‐dose rectal challenges with a difficult‐to‐neutralize simian‐human immunodeficiency virus SHIV‐SF162P3 28. As noted above, the only mosaic proteins that would have been able to elicit cross‐reactive protective responses in this vaccine were the two HIV‐1 Env glycoproteins, since the HIV‐1 Gag and Pol directed responses are unlikely to cross‐protect against the SIVmac Gag and Pol proteins of the SHIV challenge virus.…”
Section: T‐cell Vaccine Design Strategiesmentioning
confidence: 99%